How Do People Experience and Respond to Social Control From Their Partner? Three Daily Diary Studies - Scholz, Urte; Stadler, Gertraud; Berli, Corina; Lüscher, Janina; Knoll, Nina (Frontiers in Psychology, 2021)
Positive and negative forms of social control are commonly used to regulate another person’s health-related behaviors, especially in couples. Social control efforts have been shown to result in desirable, but also undesirable effects on different outcomes. Little is known for which outcomes, when, and under which contextual conditions these different effects unfold in people’s everyday lives. Using the dual-effects model of health-related social control, we predicted that same-day and previous-day positive social control would result in desirable effects on target behavior, and same-day positive control on affect. Same-day and previous-day negative control was assumed to result in undesirable effects on reactant responses (i.e., doing the opposite of what the partner wanted and hiding the unhealthy behavior), and same-day negative control on affect. Further, we explored whether it makes a difference if one or both partners intend to change their health behavior. Three daily diary studies addressed these questions for smoking (Studies 1 and 2), and physical activity (Study 3). Receiving more positive control related to more desirable target behaviour, and feeling better; more negative control was associated with more reactant responses and feeling worse. Social control unfolded its effects within one day, but hardly across days, indicating that control and its reactions to it are fast-acting processes in daily life. The pattern of results were the same for couples with one and both partners intending to change their behaviour. Further, results replicated when using partner-reported provided control. Based on these results, social control cannot be unanimously recommended as a behaviour change strategy in couples. Future studies should follow up on dyadic and temporal dynamics of social control in couples’ everyday lives in different contexts.